2023
DOI: 10.1002/jwmg.22516
|View full text |Cite
|
Sign up to set email alerts
|

Understanding implications of detection heterogeneity in wildlife abundance estimation

Jeffrey L. Laake,
Bret A. Collier

Abstract: Negative bias in mark‐recapture abundance estimators due to heterogeneity in detection (capture) probability is a well‐known problem, but we believe most biologists do not understand why heterogeneity causes bias and how bias can be reduced. We demonstrate how heterogeneity creates dependence and bias in mark‐recapture approaches to abundance estimation. In comparison, heterogeneity, and hence estimator bias, is not as problematic for distance sampling and mark‐resight methods because both techniques estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…Heterogeneity in detection probability is a consistent problem in mark‐recapture that must be appropriately accounted for to remove positive bias in abundance estimates (Laake and Collier 2024). Both approaches we used to accommodate residual heterogeneity in our DOS dataset resulted in more accurate estimates compared to the standard DOS data, but at the expense of survey precision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneity in detection probability is a consistent problem in mark‐recapture that must be appropriately accounted for to remove positive bias in abundance estimates (Laake and Collier 2024). Both approaches we used to accommodate residual heterogeneity in our DOS dataset resulted in more accurate estimates compared to the standard DOS data, but at the expense of survey precision.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than change the survey type, accuracy can be improved within a DOS sampling framework by accounting for residual heterogeneity in detection probability through detections of radio‐collared individuals (Griffin et al 2013, Hennig et al 2022) or by analyzing the dataset with a mark‐recapture distance sampling (MRDS) approach (Borchers et al 2006, Laake et al 2011, Burt et al 2014). Heterogeneity in detection probability is problematic because the sample used to estimate the observation process includes the most detectable individuals or groups; thus, estimates of detection will be biased high (Laake and Collier 2024). If the sample population contains a subset of radio‐collared individuals, one can add another capture history in the detection models that corresponds to detection of radio‐marked animals (Griffin et al 2013, Hennig et al 2022).…”
mentioning
confidence: 99%
“…The negative bias in the CMR estimates may have been a product of unmodeled heterogeneity in detection probabilities (Laake and Collier 2023). Abundance estimates based on mark-resight approaches are typically less biased because detection probabilities are based on a known number of marked animals in the population (Laake and Collier 2023). We have also found that CMR was biased low relative to mark-resight for black-tailed prairie dogs (Facka et al 2008).…”
Section: Discussionmentioning
confidence: 75%
“…We found that CMR underestimated the MNKA, although it was correlated with both MAGC and mark-resight estimates. The negative bias in the CMR estimates may have been a product of unmodeled heterogeneity in detection probabilities (Laake and Collier 2023). Abundance estimates based on mark-resight approaches are typically less biased because detection probabilities are based on a known number of marked animals in the population (Laake and Collier 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation